Therapeutic Uses and Pharmacological Properties of Shallot (Allium ascalonicum): A Systematic Review - Moldovan, Cadmiel; Frumuzachi, Oleg; Babotă, Mihai; Barros, Lillian; Mocan, Andrei; Carradori, Simone; Crişan, Gianina (Frontiers in Nutrition, 2022)
Background: Shallot (Allium ascalonicum L.) is a traditional plant species used throughout the world both for culinary purposes and as a folk remedy. To date (i.e., April 2022), there is no report on the main pharmacological activities exerted by shallot preparations and/or extracts. Scope and Approach: The aim of this study was to comprehensively review the pharmacological activities exerted by shallot, with rigorous inclusion and exclusion criteria based on the scientific rigor of studies. Prisma guidelines were followed to perform the literature search. Key Findings and Conclusions: The literature search yielded 2,410 articles of which 116 passed the required rigorous criteria for inclusion in this review. The extracts exert a potent antioxidant activity both in vitro and in vivo, as well as a strong inhibitory capacity on various pathogens with relevant implications for public health. Moreover, shallot can be used as adjuvant therapy in cardiovascular diseases, diabetes, cancer prevention, and other non-communicable diseases associated with inflammatory and oxidative pathways. Future studies investigating the chemical composition of this species, as well as the molecular mechanisms involved in the empirically observed pharmacological actions are required.